Cluster analysis of speed run, bounding run and skipping exercises - Ciacci, S.; Merni, F. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study is to find analogies and differences among 3 different skills: speed run and two special exercises (bounding run and skipping). Three correlation patterns have been created, each for one of the 3 skills, every pattern takes origin by multivariate analysis (cluster analysis), using the same 12 variables. All these variables (spatial, temporal and kinematic) are relative to the Center of Mass (COM). Eight athletes were analyzed and the system used to get the data was the Vicon Motion System (3D optoelectronics system). The analysis has shown that only few variables of the 3 patterns are correlated in the same way, these few variables must to be taken into consideration to develop the running performance through these special exercises.